Actual Autonomy, Efficiency and Performance of Universities: Insights from the Russian Case. Issue 2 (25th January 2022) - Agasisti, Tommaso; Shibanova, Ekaterina
ABSTRACT: This paper studies the relationship between university institutional autonomy (both formal and informal) and their performance and efficiency using multi-stage empirical methodology. First, we measure an "autonomy-in-use" index, and then we employ Data Envelopment Analysis in order to evaluate institutional efficiency. Lastly, we use a panel fixed effect regression to provide robust evidence for the relationship between institutional autonomy, performance and efficiency. We find that formal status of autonomy does not predict higher publication activity or efficiency. However, the findings also reveal that informal autonomy is positively associated with efficiency scores, and advanced practices in staff management can contribute to increases in publication activity and overall institutional efficiency.